Peripartum Ruptured Uterine Angioleiomyoma - Nora Mohamed; Ayman Almasalma (Gynecology Obstetrics & Reproductive Medicine)
Uterine angioleiomyoma is a rare entity. Angioleiomyoma is a benign vascular tumor that originates from the blood vessels. Although exceptionally they can be found in the uterus, they are commonly reported in the lower extremity. Preoperative diagnosis is tricky. We are publishing this case to highlight uterine contractions as a possible cause of the peripartum rupture.